Factors Affecting Anemia in Pregnant Women in Ratna Clinic - Muthia Sari Mardha; Endriyani Syafitri (JURNAL PROTEKSI KESEHATAN, 2021)
Anemia in the first trimester of pregnancy can cause abortion, missed abortion and congenital abnormalities, in the second trimester it causes premature labor, antepartum bleeding, impaired fetal growth in utero, asphyxia, LBW, low IQ and even infant death. the research objective was to determine the factors that influence anemia in pregnant women at Ratna Clinic. This research is an analytic survey with a cross sectional research design. The dependent variable used was the incidence of anemia and the independent variables were age, parity, ANC visit, knowledge and opinion. The population of this study were all pregnant women who were in the clinic ratna 123 people. The sample in this study amounted to 55 respondents. The sampling technique uses the Accidental Sampling technique. The results of the study on 55 respondents, most of whom did not experience anemia (normal) as many as 33 respondents (60%) and a small proportion had mild anemia as many as 6 respondents (10.9%). The conclusion from the research results is that there is no relationship between age, parity on anemia in pregnant women at the Kuta Baro Aceh Besar Community Health Center and ANC visits (p-value 0.002), knowledge (p-value 0.001) and income (0.009) on anemia in pregnant women at Ratna's Clinic. After conducting multivariate analysis, it was found that the ANC visit variable had the most influence on the incidence of anemia in pregnant women. The clinic leadership should make a policy and improve the quality of services for pregnant women by implementing and providing information to pregnant women about anemia prevention.